A Model-Driven Approach for the Design of Web Information Systems based on Frameworks - Martins, Beatriz Franco; Souza, Vítor E. Silva (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2015: Proceedings of the 21st Brazilian Symposium on Multimedia and the Web, 2015)
In the field of Web Engineering, many methods have been proposed. FrameWeb is a method that targets the development of systems that use certain kinds of frameworks in their architecture, proposing the use of models that incorporate concepts from these frameworks during design. However, in its original proposal, FrameWeb’s models do not fit well different framework instances, its language is not formally defined and no tool support is offered to aid software architects in creating the models. In this paper, we propose to address these issues using model-driven techniques.